(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: This article explores the role of motivation in learning English at the secondary school level. Based on academic research and personal observations, it argues that motivation is one of the most significant factors influencing students’ success in English language acquisition. Both intrinsic and extrinsic motivation play unique roles, and teachers, classroom climate, and learning strategies also contribute. Personal experiences and reflections are included to show how motivation affects actual learning outcomes and student engagement.